Korelasi Lingkar Lengan Atas dan Lingkar Betis sebagai Prediktor Sarkopenia dengan Kadar IGF-1 pada Kelompok Lanjut Usia - Triyana Sari; Erik Sidharta; Alexander Halim Santoso; Yohanes Firmansyah; Edwin Destra; Farell Christian Gunaidi; Angel Sharon Suros; Naufal Rayhan (Lembaga Pengembangan Kinerja Dosen, 2025)
Sarcopenia is a common condition among the elderly. Identifying individual risk factors associated with sarcopenia is essential for developing effective prevention strategies. This cross-sectional study aimed to investigate the association between insulin-like growth factor (IGF) levels and the incidence of sarcopenia, as assessed through mid-upper arm circumference and calf circumference, among older adults residing at Panti Werdha Bina Bhakti. Anthropometric measurements were obtained using a standard measuring tape, while IGF levels were measured through venous blood sampling and analyzed in a laboratory setting. Statistical analysis was performed using the Spearman correlation test. The study found that the average age of participants was 74.34 years, with 84.1% being female. The mean mid-upper arm circumference was 23.73 cm, and the mean calf circumference was 28.58 cm. The average IGF level was 14.43. Spearman’s rho analysis revealed a significant correlation between mid-upper arm and calf circumferences (r = 0.550; p < 0.001), as well as between mid-upper arm circumference and IGF levels (r = 0.237; p = 0.032). However, no significant correlation was observed between calf circumference and IGF levels (r = 0.176; p = 0.114). In conclusion, mid-upper arm circumference was significantly correlated with both calf circumference and IGF levels, whereas calf circumference showed no significant correlation with IGF in this elderly population. Keywords: Calf Circumference, Mid-Upper Arm Circumference, Older adults, Sarcopenia